A major QTL identification and candidate gene analysis of watermelon fruit cracking using QTL-seq and RNA-seq - Zhan, Yuanfeng; Hu, Wei; He, Huang; Dang, Xuanmin; Chen, Songbi; Bie, Zhilong (Frontiers in Plant Science, 2023)
Fruit cracking decrease the total production and the commercial value of watermelon. The molecular mechanisms of fruit cracking are unknown. In this study, 164 recombinant inbred lines (RILs) of watermelon, derived from the crossing of WQ1 (cracking-sensitive) and WQ2 (cracking-tolerant) lines, were sequenced using specific length amplified fragment sequencing (SLAF-seq). A high-density genetic linkage map was constructed with 3335 markers spanning 1322.74 cM, at an average 0.40 cM across whole-genome flanking markers. Cracking tolerance capacity (CTC), depth of fruit cracking (DFC), rind thickness (RT), and rind hardness (RH) were measured for quantitative trait locus (QTL) analysis. For the four traits analyzed, one major QTL with high phenotypic variation explained (41.04%–61.37%) was detected at 76.613–76.919 cM on chromosome 2, which contained 104 annotated genes. Differential gene expression analysis with RNA-seq data between the two parents identified 4508 differentially expressed genes (DEGs). Comparison of the genes between the QTL region and DEGs, 8 coexisting genes were obtained. qRT-PCR analysis revealed that these genes were significant differentially expressed between the two parents. These results give new insights into identifying QTLs or genes and marker-assisted breeding in watermelon.